ANALYSIS OF PRODUCT QUALITY AND PRODUCT INNOVATION ON CONSUMER LOYALTY OF CONVECTION COMPANIES - Nurminingsih; Rahayu Somalua; Mei Supriyani; Hammad Bawazir (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
In today's competitive marketplace, businesses face the ongoing challenge of fostering consumer loyalty to sustain their market presence and growth. The purpose of this study is to examine the effect of Product Quality and Product Innovation on Consumer Loyalty of Fizzul Putra Mandiri Convection in Jombang Regency. The study population consists of consumers from Fizzul Putra Mandiri Convection in Jombang Regency, specifically regular customers. This research employs a quantitative approach, with a fixed sample size of 85 regular consumers. Drawing from information provided by Fizzul Putra Mandiri Convection, the sampling method utilizes the saturated sample technique, encompassing the entire population as respondents. Data were collected through a questionnaire and processed using the Structural Equation Model (SEM) with SmartPLS 3 software. The results revealed that product quality had an insignificantly positive effect on consumer loyalty. This suggests that higher product quality is associated with increased consumer loyalty, though the effect is not statistically significant. In other words, a minor increase in product quality leads to a slight rise in consumer loyalty, and a slight decrease in product quality results in a slight decrease in consumer loyalty. Conversely, product innovation significantly and positively influences consumer loyalty, indicating that higher levels of product innovation led to higher consumer loyalty, while lower levels of product innovation result in lower consumer loyalty. Additionally, the study demonstrates a positive and significant correlation between product quality and product innovation. This suggests that higher product quality is linked to greater product innovation, whereas lower product quality is associated with reduced product innovation.